Kerugian Daerah, Kesejahteraan Masyarakat dan Opini Pemeriksaan atas Laporan Keuangan Pemerintah Daerah di Indonesia - Sigit Istiyanto (Jurnal Akuntansi dan Bisnis, 2016)
This study aims to obtain empirical evidence about the effect of regions loss (the number and value of the findings of regions loss) and social welfare (HDI, the GDP per capita, and the level of income disparity) to the financial statements opinion of the local government. This study uses purposive sampling. The sample used in this study is as much as 158 local government audited by BPK in 2013 and 2014. This study uses multiple linear regression analysis to test the classical assumption that includes data normality, heteroscedasticity, and multicollinearity test using the pro-gram Statistical Package for the Social Science (SPSS). The test results showed that the loss of area significantly influence the financial statements opinion of the local government, while the number of findings loss of area, HDI, the GDP per capita, and the level of income disparity does not affect the financial statements opinion of the local government.x`